Long-lasting clinical, radiological and immunological remission of severe nasal polyposis by means of 'reboot' surgery. Issue 4 (2nd April 2020) - Malvezzi, Luca; Pirola, Francesca; De Virgilio, Armando; Heffler, Enrico
Abstract : A 68-year-old woman with a long history of relapsing chronic rhinosinusitis with nasal polyps (CRSwNP) underwent a complete reboot surgery and nasal biopsy prior to and after surgery. Remarkable improvement of symptoms and no signs of mucosal oedema and no complaints of initially worsening nasal functions were still present 12 months after reboot surgery. Biopsy demonstrated an outstanding reduction in eosinophilic infiltration and re-epithelisation of nasal mucosa with normal features after reboot approach compared with previous surgeries. Therefore, reboot approach may become an effective instrument in plurioperated patients with CRSwNP who suffer from a nasal condition that is recalcitrant to pharmacological therapies and is unsatisfactorily treated by standard surgical techniques.